Limbic Responses Following Shock Wave Exposure in Male and Female Mice - McNamara, Eileen H.; Tucker, Laura B.; Liu, Jiong; Fu, Amanda H.; Kim, Yeonho; Vu, Patricia A.; McCabe, Joseph T. (Frontiers in Behavioral Neuroscience, 2022)
Blast traumatic brain injury (bTBI) presents a serious threat to military personnel and often results in psychiatric conditions related to limbic system dysfunction. In this study, the functional outcomes for anxiety- and depressive-like behaviors and neuronal activation were evaluated in male and female mice after exposure to an Advanced Blast Simulator (ABS) shock wave. Mice were placed in a ventrally exposed orientation inside of the ABS test section and received primary and tertiary shock wave insults of approximately 15 psi peak pressure. Evans blue staining indicated cases of evident blood-brain barrier breach in the superficial cerebral cortex four, but not 24 hours after blast, but sampling suggested the severity was variable. Behavioral testing with the elevated plus maze (EPM) or elevated zero maze (EZM), sucrose preference test (SPT), and tail suspension test (TST) or forced swim test (FST) were conducted 8 days ̶ 3.5 weeks after shock wave exposure. There was a sex difference, but no injury effect, for distance travelled in the EZM where female mice travelled significantly farther than males. The SPT and FST did not indicate group differences; however, injured mice were less immobile than sham mice during the TST. In summary, mice did not display significantly increased anxiety- or depressive-like behavior after single shock wave exposure, but demonstrated less immobility during the TST; possibly indicating more agitated behavior. In a separate cohort of animals, the expression of the immediate early gene, c-Fos, was detected four hours after undergoing the same procedures. No differences in c-Fos expression were apparent in the cerebral cortex, but female mice in general displayed enhanced c-Fos activation in the paraventricular nucleus of the thalamus (PVT) compared to male mice. In the amygdala, more c-Fos-positive cells were observed in injured animals compared to sham mice. The observed sex differences in the PVT and c-Fos activation in the amygdala may correlate with the reported hyperactivity of females post-injury. This study demonstrates, albeit with mild effects, behavioral and neuronal activation correlates in female rodents after blast injury that could be relevant to the incidence of increased post-traumatic stress disorder in women.